HUBUNGAN KUALITAS KIE BIDAN SAAT P4K (PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI) DENGAN PERSIAPAN IBU HAMIL DALAM PERENCANAAN PERSALINAN DI PUSKESMAS MASBAGIK - Baiq Disnalia Siswari; Nurannisa Fitria Aprianti (ProHealth Journal, 2020)
Midwives as service providers at the basic and advanced levels must be able to provide good quality IEC services, including P4K services. This cross-sectional study used 88 respondents of third trimester pregnant women who had been in P4K as samples, using cluster random sampling method. Data were collected by using a questionnaire for observation. Then tabulated and analyzed with the Spearmanrenk statistical test with the help of SPSS from a computer. The results of this study 27.27% of respondents who assessed the quality of IEC performed by midwives in the good category also did labor preparation in the good category, and 28.41% of respondents gave an assessment in the sufficient category also had labor preparation in the same category. After statistical testing, it was found that there was a significant relationship between the two converted variables with a value of = 0.000 < = 0.005 with a correlation coefficient value of 0.537, which is at a moderate level. It is recommended that the Puskesmas as a place of service should conduct frequent reviews or training to maintain service quality. Midwives as officers need to improve IEC capabilities and evaluate P4K activities. Meanwhile, husbands and families can increase their participation by providing transportation, funds and blood donations for pregnant women.